Effects of Iraq/Afghanistan Deployments on Major Depression and Substance Use Disorder: Analysis of Active Duty Personnel in the US Military - Shen, Yu-Chu (American Public Health Association, 2012)
Objectives. Our objective was to analyze the association between deployment characteristics and diagnostic rates for major depression and substance use disorder among active duty personnel. Methods. Using active duty personnel serving between 2001 and 2006 (n = 678 382) and deployment information from the Contingent Tracking System, we identified individuals diagnosed with substance use disorders and major depression from TRICARE health records. We performed logistic regression analysis to assess the effect of deployment location and length on these diagnostic rates. Results. Increased odds of diagnosis with both conditions were associated with deployment to Iraq or Afghanistan compared with nondeployed personnel and with Army and Marine Corps personnel compared with Navy and Air Force personnel. Increases in the likelihood of either diagnosis with deployment length were only observed among Army personnel. Conclusions. There were increased substance use disorders and major depression across services associated with combat conditions. It would be important to assess whether the public health system has adequate resources to handle the increasing need of mental health services in this population.